The effects of rope or weighted rope jump training on strength, coordination and proprioception in adolescent female volleyball players - Ozer, D.; Duzgun, I.; Baltaci, G.; Karacan, S.; Colakoglu, F. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The aim was to assess the effects of a 12-week "rope jumping" and "weighted rope jumping" training programs on functional parameters including multi-joint coordination and proprioception, strength, endurance in adolescent female volleyball players. METHODS:Pretest posttest experimental design. Intervention: Weighted Rope Training group (N.=9; 15±1 years), Rope Training group (N.=9; 14.1±1.3 years) and Controls (N.=7; 14.4±1.3 years). Main Outcome Measures: Motor coordination, proprioception, strength and endurance of the lower extremities with concentric and eccentric performances in closed kinetic chain on multi joint system assessed by the Monitorized Squat system. Absolute average error (cm) and the standard deviation for coordination and proprioception, Peak Force (N), Total Work (Nm), Average Power (Nm/s), Maximal Speed for strength and endurance tests were calculated. Kruskal-Wallis and Mann Whitney U test were utilized. RESULTS:Weighted rope jump group had significant decrease for the deviation results of coordination on the concentric and eccentric phases for both legs (P<0.05). Rope jump and weighted rope jump groups had significantly lower results on non visible second movement deviation (P<0.05). In strength tests, the difference was found for total work that there was difference on the post assessment within groups in favour of Weighted Rope Training group in comparison to controls (P<0.05). Weighted Rope Training and control groups improved in concentric maximal speed (P<0.05). Most significant changes occured on eccentric phaese of the endurance tests that peak force increased in Weighted Rope Training group (P<0.05). CONCLUSIONS:Adding rope jump to training programs improves joint repositioning and coordination. Weighted Rope Training group got greater gains for coordination and eccentric endurance parameters for lower extremities in a closed kinetic chain.